2007
DOI: 10.1016/j.peptides.2007.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Proregion of Acanthoscelides obtectus cysteine proteinase: A novel peptide with enhanced selectivity toward endogenous enzymes

Abstract: Acanthoscelides obtectus is a devastating storage insect pest capable of causing severe bean crop losses. In order to maintain their own development, insect pest larvae feed continuously, synthesizing efficient digestive enzymes. Among them, cysteine proteinases (CPs) are commonly produced as inactive precursors (procysteines), requiring a cleavage of the peptide proregion to become active. The proregion fits tightly into the active site of procysteines, efficiently preventing their activity. In this report, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In vitro assays and artificial diets using the recombinant pro-region of the papaya proteinase IV have demonstrated a selective inhibition of digestive CysProt from several phytophagous beetles [ 24 ]. Similarly, pro-regions from two plant pest species, the nematode Heterodera glycines and the bean bruchid Acanthoscelides obtectus , efficiently inhibited their own CysProt and proteases from other herbivory species [ 25 , 26 ]. Moreover, it has been demonstrated that the CysProt pro-region from H .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assays and artificial diets using the recombinant pro-region of the papaya proteinase IV have demonstrated a selective inhibition of digestive CysProt from several phytophagous beetles [ 24 ]. Similarly, pro-regions from two plant pest species, the nematode Heterodera glycines and the bean bruchid Acanthoscelides obtectus , efficiently inhibited their own CysProt and proteases from other herbivory species [ 25 , 26 ]. Moreover, it has been demonstrated that the CysProt pro-region from H .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, C1A cysteine peptidases of Trypanosoma cruzi or Plasmodium falciparum (animal parasites) were inhibited by their cognate propeptides [17], [18]. Moreover, the cysteine peptidase activities of midgut crude soluble extracts from Colorado potato beetle or several bruchids (plant pests) were also inhibited by papaya proteinase IV propeptide or by the propeptide of a cysteine peptidase from the bean bruchid Acanthoscelides obtectus [19], [20]. Recently, it was demonstrated that genetically modified soybean expressing the propeptide of a C1A peptidase from Heterodera glycines (plant nematode pest) reduced soybean cyst nematode infection [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine proteinase inhibitors affect both the growth rate and the development of several nematodes, such as pallida [60], H. glycines [62], H. schachtti, and M. incognita [61,64], suggesting the importance of these inhibitors in the parasite digestion process. Among the different classes of proteinase inhibitors, cysteine proteinases prodomains have been described as potent inhibitors with the ability to control nematodes [53,54]. Recombinant expressed papaya proteinase IV propeptide (a plant enzyme) inhibits Colorado potato beetle cysteine peptidases [65], and synthetic propeptides inhibit Manduca sexta midgut trypsin [56].…”
Section: Effects Of the Propeptide On H Glycinesmentioning
confidence: 99%
“…The cysteine proteinase of F. hepatica (animal parasite) also was inhibited by its propeptide [27,47]. Recently, it was demonstrated that the CP propeptide of A. obtectus inhibits midgut crude soluble extract of several bruchids, such as A. obtectus, Zabrotes subfasciatus, and Callosobruchus maculatus [54], showing a broad spectrum of inhibition of the propeptide against pests of similar species.…”
Section: Effects Of the Propeptide On H Glycinesmentioning
confidence: 99%
See 1 more Smart Citation